Prognostic analysis of telangiectatic osteosarcoma of the extremities - Wei Zhong; Wei Luo; Wei Luo; Zili Lin; Ziyi Wu; Yuhao Yuan; Yizhe He (Frontiers in Oncology, 2023)
Background and objectivesTelangiectatic osteosarcoma (TOS) is a rare but highly malignant subtype of osteosarcoma. Although surgical treatment is the primary treatment modality for osteosarcoma, evidence on the benefits of different surgical methods in patients with TOS is lacking. This study aimed to compare the effects of different surgical and adjuvant treatments on overall survival of TOS, and the association of patient demographics, oncological characteristics, and socioeconomic status on treatment outcomes.MethodThis retrospective study selected the most common TOS cases of the extremities registered in the Surveillance, Epidemiology, and End Results (SEER) database from 1989 to 2019. Univariate and multivariate Cox regression models were used to analyze all prognostic factors, and Kaplan-Meier analyses were performed for disease-specific treatment factors of survival.ResultA total of 127 patients were included in the analysis. The average age at initial diagnosis was 20.09 years. In univariate analyses, the absence of metastasis at initial diagnosis, limb-salvage surgery, adjuvant chemotherapy, and no regional lymph node dissection were associated with a lower risk of death. Multivariate analysis further showed that the presence or absence of distant metastasis and regional lymph node dissection, implementation of adjuvant chemotherapy, and choice of surgical method were independent predictors of prognosis.ConclusionDistant metastasis and regional lymph node dissection are associated with poorer outcomes in TOS, and amputation has no better prognosis than limb salvage surgery. Compared with conventional chemotherapy, neoadjuvant chemotherapy did not significantly improve the prognosis of TOS.